2021
DOI: 10.1007/s10040-021-02385-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimating surface runoff and groundwater recharge in an urban catchment using a water balance approach

Abstract: Land-use changes often have significant impact on the water cycle, including changing groundwater/surface-water interactions, modifying groundwater recharge zones, and increasing risk of contamination. Surface runoff in particular is significantly impacted by land cover. As surface runoff can act as a carrier for contaminants found at the surface, it is important to characterize runoff dynamics in anthropogenic environments. In this study, the relationship between surface runoff and groundwater recharge in urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 114 publications
0
4
0
1
Order By: Relevance
“…Prominent among these processes is the partitioning of water loss between evaporation and transpiration (Lauenroth and Bradford 2006). Evapotranspiration can be estimated as the residual of precipitation ( P ), groundwater recharge (italicGWr), and natural flows (Nf) as italicGWr=PETNf (Lauenroth and Bradford 2006; Weatherl et al 2021). The historic (1973 through 2021) average rainfall was obtained from the hydrology website [https://www.dws.gov.za/Hydrology/Verified/HyStations.aspx?Region=X%26StationType=rbMeteor for Sabie‐Sand (X3), Crocodile (X2) and Komati (X1) and https://www.dws.gov.za/Hydrology/Verified/HyStations.aspx?Region=W%26StationType=rbMeteor for Usuthu (W5)].…”
Section: Resultsmentioning
confidence: 99%
“…Prominent among these processes is the partitioning of water loss between evaporation and transpiration (Lauenroth and Bradford 2006). Evapotranspiration can be estimated as the residual of precipitation ( P ), groundwater recharge (italicGWr), and natural flows (Nf) as italicGWr=PETNf (Lauenroth and Bradford 2006; Weatherl et al 2021). The historic (1973 through 2021) average rainfall was obtained from the hydrology website [https://www.dws.gov.za/Hydrology/Verified/HyStations.aspx?Region=X%26StationType=rbMeteor for Sabie‐Sand (X3), Crocodile (X2) and Komati (X1) and https://www.dws.gov.za/Hydrology/Verified/HyStations.aspx?Region=W%26StationType=rbMeteor for Usuthu (W5)].…”
Section: Resultsmentioning
confidence: 99%
“…Eini, et al 31 documented that urban texture had a significant influence on flood risk. Weatherl, et al 32 reported that runoff increase can be accompanied by AET decrease in urban areas. The positive correlation between rainfall and groundwater recharge is a good general rule 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The Sahu–Mishra–Eldho (SME) model was developed in 2010 (Sahu et al., 2010, 2012) and then modified again by Weatherl et al. (2021).…”
Section: Tiered System To Estimate Recharge At Pfas‐impacted Sitesmentioning
confidence: 99%
“…Recently, however, the SCS curve number method has been extended to simulate recharge processes more fully. The Sahu-Mishra-Eldho (SME) model was developed in 2010 (Sahu et al, 2010(Sahu et al, , 2012 and then modified again by Weatherl et al (2021).…”
Section: 14mentioning
confidence: 99%